SGLT2i treatment during AKI and its association with major adverse kidney events - Alcantar-Vallin, Luz; Zaragoza, Jose J.; Díaz-Villavicencio, Bladimir; Hernandez-Morales, Karla; Camacho-Guerrero, Jahir R.; Perez-Venegas, Miguel A.; Carmona-Morales, Edgar J.; Oseguera-Gonzalez, Alexa N.; Murguia-Soto, Cesar; Chávez-Alonso, Gael; Arredondo-Dubois, José M.; Orozco-Chan, Carlos E.; et al. (Frontiers in Pharmacology, 2024)
Background The association between the administration of sodium–glucose cotransporter 2 inhibitors (SGLT2is) during acute kidney injury (AKI) and the incidence of major adverse kidney events (MAKEs) is not known. Methods This retrospective cohort study included patients with AKI and compared the outcomes for those who were treated with SGLT2is during hospitalization and those without SGLT2i treatment. The associations of SGLT2i use with MAKEs at 10 and 30–90 days, each individual MAKE component, and the pre-specified patient subgroups were analyzed. Results From 2021 to 2023, 374 patients were included in the study—316 without SGLT2i use and 58 with SGLT2i use. Patients who were treated with SGLT2is were older; had a greater prevalence of diabetes, hypertension, chronic heart failure, and chronic kidney disease; required hemodialysis less often; and presented stage 3 AKI less frequently than those who were not treated with SGLT2is. Logistic regression analysis with nearest-neighbor matching revealed that SGLT2i use was not associated with the risk of MAKE10 (OR 1.08 [0.45–2.56]) or with MAKE30–90 (OR 0.76 [0.42–1.36]). For death, the stepwise approach demonstrated that SGLT2i use was associated with a reduced risk (OR 0.08; 0.01–0.64), and no effect was found for kidney replacement therapy (KRT). The subgroups of patients who experienced a reduction in the risk of MAKEs in patients with AKI treated with SGLT2is were those older than 61 years, those with an eGFR >81, and those without a history of hypertension or DM (p ≤ 0.05 for all). Conclusion The use of SGLT2is during AKI had no effect on short- or medium-term MAKEs, but some subgroups of patients may have experienced benefits from SGLT2i treatment.